2021
DOI: 10.3390/ijerph18126576
|View full text |Cite
|
Sign up to set email alerts
|

Reproductive Health Risks Associated with Occupational and Environmental Exposure to Pesticides

Abstract: A marked reduction in fertility and an increase in adverse reproductive outcomes during the last few decades have been associated with occupational and environmental chemical exposures. Exposure to different types of pesticides may increase the risks of chronic diseases, such as diabetes, cancer, and neurodegenerative disease, but also of reduced fertility and birth defects. Both occupational and environmental exposures to pesticides are important, as many are endocrine disruptors, which means that even very l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
34
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(36 citation statements)
references
References 143 publications
(151 reference statements)
1
34
0
1
Order By: Relevance
“…And, PTS was also proven to effectively protect oocyte maturation against CPF-mediated defects (Figure 7). Nowadays, the usage of OP insecticides remains worldwide and leads to the serious environmental problem (Fucic et al, 2021). Previous studies have shown that OP insecticides can make the loss of cell function and cause the defects to cells, and CPF could exert the detrimental effects to the reproductive system and the toxicology to oocytes (Nishi and Hundal, 2013;Li et al, 2015;Jiang et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…And, PTS was also proven to effectively protect oocyte maturation against CPF-mediated defects (Figure 7). Nowadays, the usage of OP insecticides remains worldwide and leads to the serious environmental problem (Fucic et al, 2021). Previous studies have shown that OP insecticides can make the loss of cell function and cause the defects to cells, and CPF could exert the detrimental effects to the reproductive system and the toxicology to oocytes (Nishi and Hundal, 2013;Li et al, 2015;Jiang et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Reproductive toxicity is considered as a most common pathological cause of mammalian infertility (Mourikes and Flaws, 2021). It has been reported that with the wide use of pesticides in the control of agriculture and residential pests, organophosphate (OP) insecticides, a largest and most diverse group, cause the adverse effects on the reproductive system of consumers (Fucic et al, 2021). An increasing number of reports has demonstrated that OP insecticides destroy the functions of ovary and testis, and increase the risk of infertility (Nishi and Hundal, 2013;Abdel-Razik et al, 2021;Ubaid Ur Rahman et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, it should also be acknowledged that such chemical pollutants do not just impact male reproduction. They are also thought to be responsible for a wide variety of reproductive problems in women, from impaired endometrial receptivity and failed embryo implantation to abnormalities of sexual development, complications of pregnancy and birth defects ( Caserta et al , 2021 ; Fucic et al 2021 ).…”
Section: Why Are Human Fertility Rates In Decline?mentioning
confidence: 99%
“…As regards chronic health effects, the evidence is inconsistent, and the mechanisms involved are unclear (7,8). In several human studies, pesticides have been shown to be related to chronic adverse effects on the immune, neurological, respiratory, endocrine, and reproductive systems (7,(10)(11)(12)(13)(14)(15)(16). Symptoms indicating neurobehavioral, motor, and sensory dysfunction, have been reviewed in some symptom prevalence studies (11,(17)(18)(19).…”
Section: Introductionmentioning
confidence: 99%